Preparation method of protein amido straw cellulose salt-absorbing and water-retaining composite material

By preparing a straw cellulose-based salt-absorbing and water-retaining composite material containing amide bonds, the problems of high preparation cost and environmental pollution of feather and straw materials were solved, achieving the effects of saline-alkali land improvement and soil carbonization, while the material is biodegradable.

CN121064644APending Publication Date: 2025-12-05SHIHEZI UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511140541.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-15
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

Existing technologies for preparing water-absorbing and water-retaining materials using feathers and straw have problems such as high cost and environmental pollution, and straw cellulose requires additional nitrogen during degradation in soil.

Method used

By polymerizing waste feather protein with straw cellulose and adding environmentally friendly active substances, a straw cellulose-based salt-absorbing and water-retaining composite material containing amide bonds is prepared. The material has self-sufficient biodegradability, and the preparation process is simple and inexpensive.

Benefits of technology

The material achieves salt absorption and water retention functions, reduces the harm of agricultural chemicals to the soil, is suitable for saline-alkali land improvement and soil carbon enrichment and fertilization, and the material is completely biodegradable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121064644A_ABST
    Figure CN121064644A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of straw resource utilization, and discloses a preparation method of a protein amido straw cellulose salt-absorbing and water-retaining composite material. The straw cellulose-based salt-absorbing and water-retaining composite material containing amido bonds is prepared by obtaining micromolecular amino acid containing a large number of amido bonds from waste feather protein, then prepolymerizing the micromolecular amino acid with hydroxyl of straw cellulose and adding an environment-friendly active substance with a water-retaining function, and the material contains nitrogen in a certain proportion, can realize self-contained biodegradation and has a good water-retaining effect. The method can be applied to saline-alkali soil improvement and soil recarburization and fertility improvement, and harm of agricultural chemicals to soil is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of straw resource utilization, and particularly relates to a preparation method of a protein amide-based straw cellulose salt-absorbing and water-retaining composite material. BACKGROUND

[0002] Animal fur waste contains a large amount of protein. Amino acids in the protein contain characteristic functional groups of amino (-NH2) and carboxyl (-COOH), can form peptide bonds through dehydration condensation, assemble into protein macromolecular chains, and can be linked between molecules through hydrogen bonds to increase the stability of the macromolecular chains. The carboxyl and amino groups in the amino acid amide bond belong to hydrophilic groups and have a certain water absorption and water retention capacity. Therefore, the protein can be used to prepare a natural high molecular material with water absorption and water retention. In view of the efficient utilization of feather protein resources, researches have been carried out on the extraction of protein from these wastes, the modification of protein, the preparation of protein-based biosorbent materials and the like. Patent CN202411153020.2 discloses a keratin-based biological adhesive prepared from waste feathers and a preparation method thereof. The adhesive is prepared by oxidizing and modifying feather keratin and reassembling keratin disulfide bonds. Patent CN202210232798.7 discloses a high water-absorbing fiber based on feather protein and a preparation method thereof. The environmentally friendly high water-absorbing fiber is prepared by compounding and polymerizing animal feathers, acrylic acid, maleic acid, an initiator and a crosslinking agent. Although the above methods realize the comprehensive utilization of feather waste, there is still a problem of high cost of preparation or treatment and application.

[0003] In addition, a large amount of straw waste is generated in agricultural production, and straw mainly contains 30-50% of cellulose, which has hydrophilic hydroxyl groups in its chemical structure and can participate in chemical reactions to realize the chemical modification function of straw fibers. Patent CN202111513908.9 discloses a kind of straw-based water-absorbing water-retaining agent and its preparation method, which is pretreated by urea alkali solution, and then the straw cellulose is separated out, then formaldehyde and urea are added for polycondensation reaction, and a straw-based water-retaining agent with three-dimensional space network is prepared. Patent CN202310667396.4 discloses a preparation method of modified corn straw cellulose-based water-absorbing water-retaining agent, which is treated by alkali solution to obtain cellulose suspension, then sodium chlorite and acetic acid mixed solution are added, and the reaction is carried out under water bath condition, then the straw cellulose is added, and the initiator, acrylic acid and crosslinking agent are added for free radical polymerization reaction, and the straw-based water-retaining agent is obtained after the solid material is dried. Patent CN202411188231.X discloses a degradable corn straw biomass-based water-retaining agent, its preparation method and application, which is prepared by microwave hydrothermal and alkali activation of crushed corn straw to obtain biomass porous carbon, then polyacrylamide and sodium carboxymethyl cellulose are added, and the initiator and crosslinking agent are added to prepare a biodegradable biomass-based water-retaining agent. Although straw cellulose is widely available and environmentally friendly, the current pretreatment and synthesis method still adds a large amount of alkali solution, which will produce potential pollutants that pollute the environment during material processing, and the degradation of straw cellulose in soil requires additional nitrogen elements.

[0004] Therefore, the present application patent obtains a small molecule amino acid containing a large number of amide bonds from waste feather protein, then prepolymers with the hydroxyl group of straw cellulose, and adds an environmentally friendly active substance with water-retaining function to prepare a straw cellulose-based salt-absorbing water-retaining composite material containing amide bonds. The material has a certain proportion of nitrogen, can realize self-sufficient biodegradation, has good salt-absorbing water-retaining function, and has simple preparation process and low cost, which can be widely applied to saline-alkali soil improvement. SUMMARY

[0005] The present application uses the solubility depolymerization small molecule substance of waste feather protein to polymerize with straw cellulose monomers to form a composite material with salt-absorbing water-retaining property. The material is environmentally friendly, can be applied to saline-alkali soil improvement and soil carbon increase and fertilization, and can reduce the harm of agricultural chemicals to soil.

[0006] The technical scheme of the present application is as follows:

[0007] A preparation method of a protein amide-based polymerized straw cellulose salt-absorbing water-retaining composite material, the steps are as follows:

[0008] (1) Preparation of the protein amide group-containing straw cellulose material: 50-100 parts of crushed waste animal fur protein is taken, and 5-10 parts, 10-30 parts, 1-5 parts, 1-5 parts, 1-2 parts, 2-3 parts of urea, sodium thiosulfate, dithiothreitol, sodium hydroxide, polyvinyl alcohol, and sodium persulfate are sequentially added, 20-50 parts of ultrapure water is added, and the mixture is reacted at 60-90°C under nitrogen for 10-12h, and then filtered to obtain a soluble liquid A containing feather protein; 100-200 parts of crushed straw is taken, 1-10 parts of urea, 1-2 parts of sodium hydroxide, 1-5 parts of ammonium persulfate, and 1-5 parts of dibenzoyl peroxide are added, 200-500 parts of ultrapure water is added, and the mixture is fully reacted at 50-60°C for 10-20h, and then filtered to obtain a solid straw cellulose, then the soluble liquid A and 1-2 parts of cerium nitrate ammonium are added, and the mixture is reacted at 25-35°C for 3-8h, and then filtered and dried at 50°C for 24-48h to obtain the protein amide group-containing straw cellulose material B.

[0009] (2) Preparation of the salt-absorbing and water-retaining composite material: 50-100 parts of the protein amide group-containing straw cellulose material B is taken, 100-400 parts of ultrapure water is added, and 1-5 parts of citric acid, 1-2 parts of ferrous ammonium sulfate, 1-5 parts of ammonium persulfate, 5-10 parts of acrylic acid, and 1-5 parts of epichlorohydrin are sequentially added, and the mixture is reacted at 50-60°C for 5-10h, and then subjected to solid-liquid separation, washed with ultrapure water, and dried at 50°C for 24-48h to obtain the protein amide group-containing polymer straw cellulose salt-absorbing and water-retaining composite material. The conditions for preparing the material are optimized according to the salt-absorbing and water-retaining performance of the composite material.

[0010] The waste animal fur includes the fur of chickens, ducks, and other farmed animals, and the fur of pigs and cows, and needs to be crushed to less than 5mm by a crusher.

[0011] The straw includes the straw of corn, wheat, rice, and cotton, and needs to be crushed to less than 2.0mm by a crusher.

[0012] The salt-absorbing and water-retaining performance of the material is tested by calculating the NaCl and water content absorbed by each gram of the composite material within 10h.

[0013] The protein amide group-containing straw cellulose salt-absorbing and water-retaining composite material is prepared, the preparation process of the composite material is simple, the cost is low, the material can be completely biodegraded, the material can absorb salt in the soil, hold soil moisture, slow down soil moisture evaporation, reduce the residue of organic pollutants in the soil, and the like, and the material can be applied to the improvement of saline-alkali land and the protection of soil ecology. BRIEF DESCRIPTION OF DRAWINGS

[0014] Figure 1 The salt-absorbing and water-retaining performance of the composite material is not related to the amount of straw.

[0015] Figure 2 are the salt absorption and water retention properties of the composite materials under different amounts of acrylic acid.

[0016] Figure 3 are the salt absorption properties of the composite materials under different reaction times. DETAILED DESCRIPTION

[0017] The specific embodiments of the present application are further illustrated below in conjunction with the accompanying drawings and technical solutions.

[0018] Example 1: Effect of different straw amounts on the salt absorption and water retention properties of the composite materials

[0019] Take 50g of waste feather protein, crush it to less than 5mm with a crusher, and add 5g, 10g, 1g, 5g, 1g, and 2g of urea, sodium thiosulfate, dithiothreitol, sodium hydroxide, polyvinyl alcohol, and sodium persulfate, respectively. Add 50mL of ultrapure water, and react under nitrogen protection at 90℃ for 10h, then filter to obtain a soluble liquid containing feather protein A; repeat the above preparation process 3 times.

[0020] Take 100g, 150g, and 200g of crushed corn straw (2.0mm) respectively, and add 5g of urea, 2g of sodium hydroxide, 1g of ammonium persulfate, and 2g of dibenzoyl peroxide in sequence, then add 300mL of ultrapure water, and react at 50℃ for 15h. After filtering, a solid straw cellulose is obtained, then 1 part of the above prepared soluble liquid and 1.0g of cerium nitrate are added, and reacted at 35℃ for 5h. After filtering, it is dried at 50℃ for 24h to obtain protein amide group-containing straw cellulose materials B1 (100g), B2 (150g), and B3 (200g).

[0021] Take the above prepared protein amide group-containing straw cellulose materials B1, B2, and B3, and add 10g of citric acid, 4g of ferrous ammonium sulfate, 10g of ammonium persulfate, 20g of acrylic acid, and 10g of epichlorohydrin in sequence, and react at 60℃ for 5h. After filtering, it is washed with ultrapure water, and dried at 50℃ for 48h to obtain protein amide group-containing polymeric straw cellulose salt absorption and water retention composite materials C1 (100g), C2 (150g), and C3 (200g).

[0022] Take 1.0g of the original straw and the prepared composite materials C1, C2, and C3, and add them to salt water containing 10g / L of NaCl. After standing for 10h, the amount of salt ions and water absorbed by the original straw and the composite materials are measured, as shown in Table 1. Figure 1As shown, compared with the original straw control, when the amount of straw is 100g, 150g, 200g, the salt absorption of the composite material is increased by 156%, 229% and 215% respectively; the water absorption is increased by 43.9%, 65.8% and 51.2% respectively. These results show that with the increase of the amount of straw, the salt absorption and water absorption capacity of the composite material as a whole shows an increasing trend, when the amount of straw material is 150g, i.e. the ratio of waste feather protein and straw is 1:3, the performance of the prepared composite material is best.

[0023] Example 2 Effect of the amount of acrylic acid on the salt absorption and water retention performance of the composite material

[0024] Take 100g of crushed waste feather protein, crush it to less than 5mm with a crusher, and add 10g, 18g, 2g, 8g, 2g, 2.5g of urea, sodium thiosulfate, dithiothreitol, sodium hydroxide, polyvinyl alcohol, and sodium persulfate respectively, add 100mL of ultrapure water, and react at 90℃ for 12h under nitrogen protection, then filter to obtain soluble liquid A containing feather protein; repeat the above preparation process 3 times.

[0025] Take 200g of crushed corn straw, and add 5g of urea, 2g of sodium hydroxide, 1g of ammonium persulfate, and 2g of dibenzoyl peroxide in sequence, then add 300mL of ultrapure water, and react at 50℃ for 20h, then filter to obtain solid straw cellulose, then add 1 part of the above prepared soluble liquid and 1g of cerium nitrate, and react at 35℃ for 5h, then filter and dry at 50℃ for 24h to obtain protein amide group-containing straw cellulose material B. Repeat the above process 3 times.

[0026] Take 3 parts of the above prepared protein amide group-containing straw cellulose material B, and add 300mL of ultrapure water, then add 10g of citric acid, 4g of ferrous ammonium sulfate, 10g of ammonium persulfate, and 10g of epichlorohydrin in sequence, and add 10g, 15g, and 20g of acrylic acid respectively, and react at 60℃ for 5h, then filter, wash with ultrapure water, and dry at 50℃ for 48h to obtain protein amide group-containing polymeric straw cellulose salt absorption and water retention composite material C1(10g), C2(15g), and C3(20g).

[0027] Take 1.0g of the original straw and the prepared composite materials C1, C2, and C3, and add them to salt water containing 10g / L of NaCl, with 3 replicates for each treatment, and measure the amount of salt ions and water absorbed by the original straw and the composite materials after standing for 10h, as shown in Table 2. Figure 2As shown, compared with the original straw control, when the amount of acrylic acid is 10 g, 15 g, and 20 g, the salt absorption of the composite material is increased by 135%, 208%, and 256%, respectively; the water absorption is increased by 26.5%, 58.5%, and 73.1%, respectively. These results show that with the increase of the amount of acrylic acid, the salt absorption and water absorption capacity of the composite material as a whole shows an increasing trend.

[0028] Example 3 Influence of different reaction times on the salt absorption performance of the composite material

[0029] Take 50 g of crushed waste feather protein, crush it to less than 5 mm with a crusher, and add 5 g, 10 g, 1 g, 5 g, 1 g, and 2 g of urea, sodium thiosulfate, dithiothreitol, sodium hydroxide, polyvinyl alcohol, and sodium persulfate, respectively. Add 50 mL of ultrapure water, and under the condition of nitrogen protection, react at 90°C for 10 h, then filter to obtain a soluble liquid containing feather protein A; repeat the preparation process 3 times according to the above process.

[0030] Take 100 g of crushed corn straw in three portions, and add 5 g of urea, 2 g of sodium hydroxide, 1 g of ammonium persulfate, and 2 g of dibenzoyl peroxide, respectively, then add 300 mL of ultrapure water, and react at 50°C for 15 h. After filtration, solid straw cellulose is obtained, then add 1 portion of the above prepared soluble liquid and 1.0 g of cerium nitrate, and react at 35°C for 3 h, 5 h, and 8 h, respectively. After filtration, dry at 50°C for 24 h to obtain protein amide-containing straw cellulose materials B1 (3 h), B2 (5 h), and B3 (8 h).

[0031] Take the above prepared protein amide-containing straw cellulose materials B1, B2, and B3, and add 400 mL of ultrapure water, then add 10 g of citric acid, 4 g of ferrous ammonium sulfate, 10 g of ammonium persulfate, 20 g of acrylic acid, and 10 g of epoxy chloropropane in sequence, and react at 60°C for 10 h. After filtration, wash with ultrapure water, and dry at 50°C for 48 h to obtain protein amide-based polymeric straw cellulose salt absorption and water retention composite materials C1 (3 h), C2 (5 h), and C3 (8 h).

[0032] Take 1.0 g of the original straw and the prepared composite materials C1, C2, and C3, and add them to salt water containing 10 g / L of NaCl. After standing for 10 h, measure the amount of salt ions and water absorbed by the original straw and the composite materials, as shown in the following table. Figure 3 As shown, compared with the original straw control, when the reaction time is 3 h, 5 h, and 8 h, the salt absorption of the composite material is increased by 156%, 229%, and 215%, respectively. This shows that when the reaction time is 5 h, the performance of the prepared composite material is best.

Claims

1. A method for preparing a protein amide-based straw cellulose salt-absorbing and water-retaining composite material, characterized in that, The steps are as follows: (1) Preparation of protein amide group-containing straw cellulose material: 50-100 parts of crushed waste animal fur protein is taken, and 5-10 parts, 10-30 parts, 1-5 parts, 1-5 parts, 1-2 parts, 2-3 parts of urea, sodium thiosulfate, dithiothreitol, sodium hydroxide, polyvinyl alcohol, and sodium persulfate are added in turn, 20-50 parts of ultrapure water is added, and the mixture is reacted at 60-90°C under nitrogen atmosphere for 10-12h, and then filtered to obtain a soluble liquid A containing feather protein; 100-200 parts of crushed straw is taken, 1-10 parts of urea, 1-2 parts of sodium hydroxide, 1-5 parts of ammonium persulfate, and 1-5 parts of dibenzoyl peroxide are added, 200-500 parts of ultrapure water is added, and the mixture is reacted at 50-60°C for 10-20h, and then filtered to obtain solid straw cellulose, then soluble liquid A and 1-2 parts of cerous nitrate are added, and the mixture is reacted at 25-35°C for 3-8h, and then filtered and dried at 50°C for 24-48h to obtain protein amide group-containing straw cellulose material B. (2) Preparation of salt-absorbing and water-retaining composite material: 50-100 parts of protein amide group-containing straw cellulose material B is taken, 100-400 parts of ultrapure water is added, 1-5 parts of citric acid, 1-2 parts of ferrous ammonium sulfate, 1-5 parts of ammonium persulfate, 5-10 parts of acrylic acid, and 1-5 parts of epichlorohydrin are added in turn, and the mixture is reacted at 50-60°C for 5-10h, then solid-liquid separation is performed, the material is washed with ultrapure water, and then dried at 50°C for 24-48h to obtain a protein amide group-containing polymerized straw cellulose salt-absorbing and water-retaining composite material. The conditions for preparing the material are optimized according to the salt-absorbing and water-retaining performance of the composite material.

2. The production method according to claim 1, characterized by The waste animal fur includes the hair of breeding animals such as chickens and ducks, and the fur of pigs and cows, and needs to be crushed to less than 5.0mm by a crusher.

3. The preparation method according to claim 1, characterized in that, The straw includes the straw of crops such as corn, wheat, rice, and cotton, and needs to be crushed to less than 2.0mm by a crusher. The straw includes the straw of crops such as corn, wheat, rice, and cotton, and needs to be crushed to less than 2.0mm by a crusher.

Citation Information

Patent Citations

  • Straw-based water-absorbing and water-retaining agent and preparation method thereof

    CN114106841A

  • High-water-absorption fiber based on feather protein and preparation method of high-water-absorption fiber

    CN114775091A

  • Preparation method of modified corn straw cellulose-based water-absorbing and water-retaining agent

    CN117603403A

  • Keratin-based biological adhesive prepared from waste feathers and preparation method of keratin-based biological adhesive

    CN118931492A

  • Biomass-based water-retaining agent capable of degrading corn stalks as well as preparation method and application of biomass-based water-retaining agent

    CN118978780A